Sustainable cryptocurrency adoption assessment among IT enthusiasts and cryptocurrency social communities - Yeong, Y.-C. (Elsevier Ltd, 2022)
This study sought to assess the level of Malaysian individualsâ intention to adopt cryptocurrency and intended to explore the significant drivers that predict individualsâ behavior towards the adoption of cryptocurrency. The survey data were collected from Malaysian individuals who have cryptocurrency knowledge, and the model was estimated via partial least square structural equation modeling (PLS-SEM) approach. The results manifested that the Malaysian individualsâ intention towards cryptocurrency adoption is high and the factors performance expectancy, social influence, facilitating condition and price value were found appreciably influences an individual's adoption behavior. This study can be extended by implementing or adapting this proposed research model to other countries, especially developing countries with emerging economies like Malaysia. With the distinct status of cryptocurrency legislation over nations, it can help to deepen the results of this study regarding government support as a non-predictor of an individual's behavioral intention to use cryptocurrency. Â© 2022 Elsevier Ltd